KNOWLEDGE MANAGEMENT SYSTEM SERVICE CENTER BERBASIS WEB - HAN SULAIMAN (Faktor Exacta, 2015)
Service centerisone of thecritical components inanorganization or company, especially interms of handling troubleshooting. Because increasing the number of employees of the Service Center often become busy. In this highly in need of an alternative inhandling troubleshooting.Knowledge Management can answer all of it. With the role of technology-based knowledge management system websites increasingly be felt. In this study, will be constructed of a Knowledge Management System with SECI model approach is applied to a web based service center. Usability testing on a website service center that has been created with the aim of measuring the quality of the application. In this test method is used SQA (Software Quality Assurance), blackbox, and path analyst. The variables that will be used is Communicativeness, operability, and training which is used as a benchmark the feasibility of a system. Keyword :Service Center, Knowledge Management System, SECI model.